2009
DOI: 10.1007/s11096-009-9321-0
|View full text |Cite
|
Sign up to set email alerts
|

Change of initial oral antidiabetic therapy in type 2 diabetic patients

Abstract: Objective To explore the 'real-life' therapy of type 2 diabetes mellitus with oral antidiabetic drugs (OADs). Methods From the PHARMO Record Linkage System comprising linked drug dispensing and clinical laboratory data from approximately 2.5 million individuals in the Netherlands, among others, new users of OADs were identified in the period 1999-2004. New users, aged 30 years and older, without insulin use before cohort entry date and with at least one year follow-up were included. We determined per initial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…This latter observation does not seem to be coherent as discontinuation would be associated with adequate glycaemic control; however, there will be patients restarting a different OAD shortly after discontinuing. When comparing the one-year persistence of initial OAD treatment with other published studies there was similarity with some studies [14,16], whilst there were clear differences with others [15]. The range of persistence rates can be explained by the settings where the studies were conducted, by the outcome definitions applied, and by the length of follow-up considered for the reported treatment changes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This latter observation does not seem to be coherent as discontinuation would be associated with adequate glycaemic control; however, there will be patients restarting a different OAD shortly after discontinuing. When comparing the one-year persistence of initial OAD treatment with other published studies there was similarity with some studies [14,16], whilst there were clear differences with others [15]. The range of persistence rates can be explained by the settings where the studies were conducted, by the outcome definitions applied, and by the length of follow-up considered for the reported treatment changes.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, the ADVANCE trial reported that at baseline 43% of patients were on oral monotherapy glucose lowering agent, 59% on sulfonylureas, and 38% on metformin [13]. A study conducted in PHARMO for the period 1999–2004 also reported sulfonylureas (53.2%) and metformin (40.2%) as the most frequently used initial OAD therapies [14]. Metformin use as first OAD therapy seems to be increasing in recent years in other countries as well [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a Dutch study of more than 46,000 new users of antidiabetic medicines, the proportion of patients with an addition or switch of antidiabetic treatment at 1 year ranged from 20.2% with a sulfonylurea initial treatment to 25.7% with metformin initial treatment [16]. In two earlier American studies involving 85,888 members of an American managed care organization and 19,900 members of a pharmacy benefit management organization, rates of therapeutic progression at 1 year were 24.5% [17] and 17.2% respectively [18].…”
Section: Discussionmentioning
confidence: 99%
“…As metformin SR is an alternative to metformin IR, we identified which patients would be able to switch from SoC to metformin SR and who would continue on metformin IR. Factors considered in this respect were (1) the discontinuation of metformin IR amongst newly diagnosed patients (16.1%), (2) the potential market share of metformin SR as calculated from medicine issue registries from the United Kingdom (22.53%), and (3) the percentage of patients currently on metformin IR who could be actively switched to metformin SR (0.1%) [5]. As this BIA covers multiple years, type 2 diabetes patient population growth was taken into account.…”
Section: Study Populationmentioning
confidence: 99%
“…Treatment with metformin immediate release (IR) has proven to be effective in clinical trials; however, adverse events (AEs) are a common problem. A Dutch study showed that 34.5% of the patients on metformin IR experienced AEs, and 11.4-16.1% discontinued their treatment within the first year after initiation [4,5]. Medication nonadherence, partially due to (gastrointestinal) AEs and difficult treatment regimens, is a well-known problem in type 2 diabetes patients [6].…”
Section: Introductionmentioning
confidence: 99%